Cold-Formed Steel Technology in Building Structure and its Problems as an Alternative Solution of Corrosion Resistant Structures at Coastal Areas - Prabowo Setiyawan (International Conference on Coastal and Delta Areas, 2015)
This paper aims to determine the technological development of cold-formed steel ishappening today and the problems of its application especially on the building structures. The coldformed steel structures have become alternative could be used in coastal areas due to its corrosion resistant properties. The development of the cold-formed steel use on structures is reviewed. In addition, the advantages and lacks of the cold-formed steel structural members are presented based on the research conducted previously. It is concluded that cold-formed steel technology has great potential to be developed and be applied to building structure even some problems arised have to be overcome especially regarding to local buckling and low capacity of the connection